2020
DOI: 10.3390/biomedicines8070214
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Type 1 Interferon (IFN1) Profile of Uncultured Human Bone Marrow CD45lowCD271+ Multipotential Stromal Cells (BM-MSCs): The Impact of Donor Age, Culture Expansion and IFNα and IFNβ Stimulation

Abstract: Skeletal aging is associated with reduced proliferative potential of bone marrow (BM) multipotential stromal cells (MSCs). Recent data suggest the involvement of type 1 interferon (IFN1) signalling in hematopoietic stem cell (HSC) senescence. Considering that BM-HSCs and BM-MSCs share the same BM niche, we investigated IFN1 expression profile in human BM-MSCs in relation to donor age, culture-expansion and IFN1 (α and β) stimulation. Fluorescence-activated cell sorting was used to purify uncultured BM-MSCs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…With regards to accessibility, UC is a non-invasive source of MSCs, while harvesting BM-MSCs or AD-MSCs would require a surgical procedure, could sometimes be hard to access and cause complications ( 204 ). Additionally, MSC yield and functional potential are dependent on donor factors (e.g., age and co-morbidity) ( 89 , 205 ). Several in vitro , preclinical and clinical studies remain inconclusive but suggest that the immunosuppressive function of UC-MSCs and AD-MSCs could be more potent than that of BM-MSCs ( 137 , 139 , 145 , 206 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to accessibility, UC is a non-invasive source of MSCs, while harvesting BM-MSCs or AD-MSCs would require a surgical procedure, could sometimes be hard to access and cause complications ( 204 ). Additionally, MSC yield and functional potential are dependent on donor factors (e.g., age and co-morbidity) ( 89 , 205 ). Several in vitro , preclinical and clinical studies remain inconclusive but suggest that the immunosuppressive function of UC-MSCs and AD-MSCs could be more potent than that of BM-MSCs ( 137 , 139 , 145 , 206 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to hematopoietic cells, IFN-α seems to have less effect on MSCs. The gene expression levels of differentiation markers of native MSCs were found unaffected by IFN-α ( 89 ). However, when MSCs were treated with IFN-α within an in vitro culture condition, inhibition of cell proliferation was reported ( 89 , 90 ).…”
Section: Mscs Interaction With Key Immune Cell Players In Ra and Slementioning
confidence: 99%
See 1 more Smart Citation
“…Using uncultured MSCs, our group has recently shown no significant age-related increase in adipogenic or osteogenic differentiation transcripts or ROS levels in uncultured MSCs from old donors compared to young donors [ 73 , 80 ]. This contrasts with the higher ROS levels found in minimally cultured MSCs from older donors [ 81 ].…”
Section: Age-related Changes In Mscsmentioning
confidence: 99%
“…Studies have reported a decline in their number [48,49], decline in their proliferative potential [50,51], increased bias towards adipogenesis at the expense of osteoblast formation, resulting in decline in bone formation, and enhanced fat formation [52] and decrease in migratory properties [53]. More recently, potential links have been made between the intrinsic type 1 interferon profile within MSCs and their ability to respond to DNA damage [54]. The work by Josephson et al established the effect of age-related inflammation in MSCs by demonstrating a decline in the number of MSCs and impaired bone regeneration capacity in mice models.…”
Section: Age-related Changes In Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%